Regional variation in cardiovascular mortality in Australia 2009–2012: the impact of remoteness and socioeconomic status. (23rd July 2018) - Jacobs, Jane; Peterson, Karen Louise; Allender, Steven; Alston, Laura Veronica; Nichols, Melanie
Abstract: Objective: To assess the extent to which socioeconomic status (SES) contributes to geographic disparity in cardiovascular disease (CVD) mortality. Methods: An ecological study assessed the association between remoteness and CVD mortality rates, and the mediating effect of SES on this relationship, using Australia‐wide data from 2009 to 2012. Results: Socioeconomic status explained approximately one‐quarter of the increased CVD mortality rates for females in inner and outer regional areas, and more than half of the increased CVD mortality rates in inner regional and remote/very remote areas for males, compared to major cities. After allowing for the mediating effect of SES, females living in inner regional areas and males living in remote/very remote areas had the greatest CVD mortality rates (Mortality Rate Ratio: 1.12, 95%CI 1.07–1.17; MRR: 1.15, 95%CI 1.05–1.25, respectively) compared to those in major cities. Conclusion: Socioeconomic status explained a substantial proportion of the association between where a person resides and CVD mortality rates; however, remoteness has an effect above and beyond SES for a number of subpopulations. Implications for public health: This study highlights the need to focus on both socioeconomic disadvantage and accessibility to reduce CVD mortality in regional and remote Australia.